13 - Enhanced thermal stability of cellulose nanocrystals for processing polymer nanocomposites at a high temperature - Khairatun Najwa, Mohd Amin (Elsevier, 2022)
At an industrial stage, the processing of polymer composite primarily is using a melt compounding processing approach like extrusion and injection molding. A thermoplastic polymer commonly used this process and mostly involved high processing temperature approximately from 120°C to 390°C. Typically nanocellulose like cellulose nanocrystal (CNC) which have been produced through sulphuric acid hydrolysis has poor thermal stability, thus they give rise to degradation and discoloration of the extruded nanocomposites. This chapter will be divided into two parts. The first part will review the production of nanocellulose with enhanced thermal stability and the second part will cover the nanocellulose-reinforced thermoplastic polymer nanocomposite fabricated using melt compounding technique. In the end, the potential of nanocellulose can be seen as a good potential reinforcing filler for polymer nanocomposite to be applied on an industrial scale.